1988
DOI: 10.1111/j.1471-4159.1988.tb02497.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Alteration of Various Cholinergic Markers in Cortical and Subcortical Regions of Human Brain in Alzheimer's Disease

Abstract: The main objective of the present study was to determine whether cholinergic markers (choline acetyltransferase activity and nicotinic and muscarinic receptors) are altered in Alzheimer's disease. Choline acetyltransferase activity in Alzheimer's brains was markedly reduced in various cortical areas, in the hippocampus, and in the nucleus basalis of Meynert. The maximal density of nicotinic sites, measured using the novel nicotinic radioligand N-[3H]methylcarbamylcholine, was decreased in cortical areas and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
139
0
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(156 citation statements)
references
References 44 publications
11
139
0
5
Order By: Relevance
“…The reference region was the occipital cortex where choline acetyltransferase levels from postmortem studies (McGeer et al, 1980;Araujo et al, 1988) and [ 123 I]-IBVM specific binding from an in vivo study (Kuhl et al, 1994) were found to be lowest.…”
Section: Discussionmentioning
confidence: 99%
“…The reference region was the occipital cortex where choline acetyltransferase levels from postmortem studies (McGeer et al, 1980;Araujo et al, 1988) and [ 123 I]-IBVM specific binding from an in vivo study (Kuhl et al, 1994) were found to be lowest.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Selective depletion of cholinergic neurons in the basalis of Meynert, decreased choline acetyltransferase and acetylcholinesterase activity, or down-regulation of neuronal nicotinic acetylcholine receptors suggest the roles of cholinergic deficits in Alzheimer's disease. [3][4][5][6][7][8][9][10] Donepezil, galantamine and tacrine are acetylcholinesterase inhibitors (AChEI) that have been developed for the treatment of AD under the presumption that increasing cholinergic transmission through inhibition of acetylcholinesterase will enhance cognitive function. 11,12) Donepezil is a potent and reversible acetylcholinesterase inhibitor that shows moderate improvement of cognitive function with minimal side effects 13) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Based on experiments utilizing muscarinic antagonists and/or nonselective physical or chemical lesions, cholinergic neurons projecting to the cerebral cortex and hippocampus have been identified as playing an important role in learning, memory, and attentional processes [2,3,15,19]. Moreover, in humans the loss of basal forebrain cholinergic neurons has been associated with Alzheimer's disease [1]. An understanding of the role of the basal forebrain in learning and memory has accelerated since the development of agents such as 192 IgG-saporin (SAP), that selectively lesion p75NTR-containing cholinergic neurons [9,46,48].…”
Section: Introductionmentioning
confidence: 99%